2010
DOI: 10.1136/jcp.2009.070391
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydroxyurea on the transfusion requirements in patients with severe HbE-β-thalassaemia: a genotypic and phenotypic study

Abstract: Genetic markers such as Xmn I polymorphism and alpha-gene deletions were not always beneficial for the response to hydroxyurea therapy. Thus many more markers and a larger cohort need to be studied to predict the response in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 16 publications
2
25
0
Order By: Relevance
“…Instead the Xmn 1 G c polymorphism is neither a sole nor a strong genetic determinant and hence at present cannot be used as a marker for predicting response of hydroxyurea among thalassemia intermedia patients. Our report is similar to Italia et al [19] who studied the effect of hydroxyurea on 13 Eb thalassemia patients with respect to Xmn 1 G c and found response of hydroxyurea in selected patients only.…”
Section: Discussionsupporting
confidence: 77%
“…Instead the Xmn 1 G c polymorphism is neither a sole nor a strong genetic determinant and hence at present cannot be used as a marker for predicting response of hydroxyurea among thalassemia intermedia patients. Our report is similar to Italia et al [19] who studied the effect of hydroxyurea on 13 Eb thalassemia patients with respect to Xmn 1 G c and found response of hydroxyurea in selected patients only.…”
Section: Discussionsupporting
confidence: 77%
“…This study of evaluating the role of hydroxyurea, as a clinically relevant iron chelator in removing iron from iron overloaded mice is an extension of our previous study on hydroxyurea therapy among patients with different hemoglobinopathies [4,5,11]. Our earlier work had shown that the high serum ferritin levels seen in sickle cell anemia patients [mean 1329 ± 700 ng/μl] decreased to 722 ± 578 ng/μl after two years of hydroxyurea therapy [4].…”
Section: Discussionmentioning
confidence: 96%
“…Our earlier work had shown that the high serum ferritin levels seen in sickle cell anemia patients [mean 1329 ± 700 ng/μl] decreased to 722 ± 578 ng/μl after two years of hydroxyurea therapy [4]. A statistically significant reduction in mean serum ferritin levels was also seen in β-thalassemia intermedia, β-thalassemia major and HbE-β-thalassemia patients after hydroxyurea therapy [5,11]. Another study from Iran also showed reduction in mean serum ferritin levels after one year of hydroxyurea therapy from 2751.44 ng/mL to 1594.20 ng/mL (p<0.001) in 49 β-thalassemia patients [10].…”
Section: Discussionmentioning
confidence: 99%
“…[91][92][93][94][95] Co-inheritance of a-thalassemia was described as a predictor of good response in some studies, 44,77,96 but it was found to have no effect in others. 49,68,85 Homozygosity for the XmnI polymorphism (2158C. T G g) was a strong predictor of favorable responses, 44,72,75,79,80,97 although the case was different in some studies, especially those including patients with hemoglobin E/b-thalassemia.…”
Section: Predictors Of Responsementioning
confidence: 99%
“…T G g) was a strong predictor of favorable responses, 44,72,75,79,80,97 although the case was different in some studies, especially those including patients with hemoglobin E/b-thalassemia. 65,68,70,77 A 2012 study 97 also showed that the rs766432 polymorphism at intron 2 of the BCL11A gene correlates strongly with a response to hydroxyurea therapy; further studies in this direction are encouraged. However, it is important to bear in mind that when genetic markers are studied, the markers themselves may not be causally linked to such effects, but rather variants in linkage disequilibrium with these markers may be the mediators of such effects.…”
Section: Predictors Of Responsementioning
confidence: 99%